Legal Protection for Online Shopping Business Receiving Fictive Orders With a Payment System on The Site or Cash on Delivery - Apriyanti, Devi; Purwendah, Elly Kristiani; Muchtar, Wiwin; Pudyastiwi, Elisabeth (Universitas Muhammadiyah Surabaya, 2022)
ABSTRACTÂ The implementation of buying and selling online provides many benefits to streamline time so that everyone can make buying and selling transactions wherever and whenever. However, in practice it raises several problems, such as on the Shopee shopping site with a payment system using the Cash On Delivery (COD) feature, there are obstacles that are detrimental to the seller. This obstacle is caused by consumers who do not have good intentions by disappearing suddenly when the goods arrive at the buyer's address so that the goods are not paid for and are forced to be sent back to the seller. This is clearly detrimental to the seller both in terms of material and immaterial. The focus of research in this thesis is to analyze the concept of consumer protection for Shopee sellers who implement the COD payment system. This study uses empirical juridical research methods using primary data located in Purwokerto. Data analysis techniques using qualitative methods. The results of the study show that good faith as a form of business actor's obligation to the Shopee Marketplace has been fulfilled, but there is an imbalance in the position of unilaterally canceling so that the business actor does not get his rights in the form of payment for goods. So the seller must bear the risk and the goods must be returned, and for the safety of the seller must bear the cost of resend so that COD becomes more expensive. This is referred to as the risk borne by the seller.Â Â